2022
DOI: 10.1161/atvbaha.122.317953
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Cellular Diversity and Quantitative Genome-Wide Association Study Trait Prioritization Through Single-Nuclear RNA Sequencing of the Aneurysmal Human Aorta

Abstract: Background: Mural cells in ascending aortic aneurysms undergo phenotypic changes that promote extracellular matrix destruction and structural weakening. To explore this biology, we analyzed the transcriptional features of thoracic aortic tissue. Methods: Single-nuclear RNA sequencing was performed on 13 samples from human donors, 6 with thoracic aortic aneurysm, and 7 without aneurysm. Individual transcriptomes were then clustered based on transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 139 publications
(209 reference statements)
2
26
0
Order By: Relevance
“…Enhanced TGF-b signaling is observed in the media of aortic tissues from aneurysm patients 48,49 and animal models 50 . Consistently, a recent single-nuclear RNA-seq study showed that TGFB2 expression is activated in SMC clusters of aneurysmal human aorta as compared to that of healthy control 51 . We reasoned that TGFB2 is a direct and bona fide target of PRDM16 because 1) it harbors PRDM16 ChIP-seq peaks within its proximal promoter region (Figure 2J); 2) increased Tgfb2 expression is consistently observed following Prdm16 deletion in cardiomyocytes in multiple independent studies 27,52,53 , a similar finding to our study.…”
Section: Discussionsupporting
confidence: 74%
“…Enhanced TGF-b signaling is observed in the media of aortic tissues from aneurysm patients 48,49 and animal models 50 . Consistently, a recent single-nuclear RNA-seq study showed that TGFB2 expression is activated in SMC clusters of aneurysmal human aorta as compared to that of healthy control 51 . We reasoned that TGFB2 is a direct and bona fide target of PRDM16 because 1) it harbors PRDM16 ChIP-seq peaks within its proximal promoter region (Figure 2J); 2) increased Tgfb2 expression is consistently observed following Prdm16 deletion in cardiomyocytes in multiple independent studies 27,52,53 , a similar finding to our study.…”
Section: Discussionsupporting
confidence: 74%
“…A clinical study showed that cardiovascular disease (CVD) patients with high GLRX (>0.622 ng/mL) levels were more likely to experience adverse events [63]. Recent scRNA-seq analysis of aortic aneurysms revealed that GLRX is expressed on SMCs [64]. There is a lack of research on the relationship between GLRX and AD at present.…”
Section: Discussionmentioning
confidence: 99%
“…These genes exhibited differential expression in fibroblasts and VSMC subtypes, highlighting these cellular compartments as candidates for further investigation. 30 A similar analysis for AAA-associated SNPs disclosed SORT1 as a potential pathological mediator of AAA development in VSMCs. 32 Further single-cell transcriptomic studies in individuals with other aortic phenotypes, including hereditary aortopathies, will undoubtedly help expand our understanding of the complex genetic architecture of aortic disease.…”
Section: Single-cell Transcriptomicsmentioning
confidence: 89%